An infinite family of finite ‎$‎2‎$‎-groups with deficiency zero - Hossein Abdolzadeh; Reza Sabzchi (International Journal of Group Theory, 2017)
‎‎We determine a new infinite sequence of finite $2$-groups with deficiency zero‎. ‎The groups have $2$ generators and $2$ relations‎, ‎they have coclass $3$‎ ‎and they are not metacyclic‎.